The Analysis of Speech Error in King George VI in the Movie “King’s Speech” By David Seidler - Riskiawati, Nur Sapta; Razak , Muhammad Fauzi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper explores the speech errors made by King George VI in David Seidler's